Maternal perception of spousal support in raising children with developmental disability in the context of family and child variables. Issue 3 (25th February 2022) - Kara, Tayfun; Alpgan, Ömer
Abstract: Objective: The purpose of this study was to examine the relationship between the variables of mental, physical, and emotional problems in children with developmental disabilities (DDs) and the spousal support perceived by the mothers of those children. Methods: One hundred forty‐three children diagnosed with autism spectrum disorder (ASD, n :43), intellectual disability (ID, n :28), cerebral palsy (CP, n :47),  or Down syndrome (DS, n :25) were included in this study. The support that mothers received from their spouses was evaluated using the Spousal Support Scale (SSS). Aggressive behavior in the children was evaluated using the anger‐aggression subscale of the Social Competence and Behavior Evaluation Scale (SCBE‐30). The data obtained were then subjected to statistical comparisons. Results: Multiple comparisons revealed no significant difference between the DD diagnosis groups (ID, CP, ASD, and DS) in terms of spousal support or spousal support sub‐dimension scores ( p  > 0.05). Significant negative correlation was found between anger‐aggression subscale scores and SSS sub‐parameters (emotional support r  = −0.315 p  < 0.001, financial and informational support r  = −0.285 p  < 0.001, appreciation r  = −0.299 p  < 0.001, social support r  = −0.381 p  < 0.001, and spouse support score r  = −0.389 p  < 0.001). Conclusion: Children's anger‐aggression levels were adversely affected by a lack of spousal support for their mothers.